Increasing Health Care Workers' Proficiency With Using Professional Medical Interpretation: A Workshop - Jessica Jones; Kerrilynn Rice; Victor Cueto; Coralee Del Valle Mojica; Meghan Stawitcke; Sara Salem; Elizabeth Talley; Rebecca Blankenburg (Association of American Medical Colleges, 2020)
Introduction Families with limited English proficiency are at risk for poor outcomes and medical errors due to barriers in communication. The use of professional medical interpretation has been linked to improved access to care, improved patient satisfaction, and better outcomes. However, medical interpretation remains underutilized, and the literature lacks guidelines for training health care workers in its use. This workshop aims to teach the skills needed to access and appropriately use professional medical interpretation. Methods Our team included two residents, two fellows, two faculty members, and two fellowship coordinators. This 90-minute workshop targeted at health care workers included a warm-up activity, role-play with three different types of interpretation, and large-group discussion. Anonymous evaluations were collected at the end of the workshop. Results The workshop was presented at six academic conferences (three local, one regional, and two national). Postworkshop evaluations were collected from 53 participants from multiple health care backgrounds (including medical students, residents, and physicians). The majority of participants reported that the workshop met learning objectives (98%), represented a valuable use of time (98%), and included useful handouts (92%). In addition, 90% of participants reported that the information shared in the workshop would be applied to their medical practice. Themes that emerged from postworkshop evaluations included participants' intentions to change their practice, to augment training for other providers, and to pursue institutional change. Discussion This workshop fills an important gap in medical education and provides a comprehensive orientation to interpretation resources and best practices.